(untitled) (Plant Tissue Culture and Biotechnology, 2015)
Dieback of sissoo (Dalbergia sissoo Roxb.) is a devastating plant disease, whose causative biotic agents were not yet identified unequivocally. Our previous studies revealed that bacteria belonging to the genus Pseudomonas were associated with dieback?affected sissoo trees. To study the bacterial community associated with dieback-affected sissoo trees, DNA based approaches were used in the present work. Sequencing almost the complete 16S rRNA gene of 33 selected Pseudomonas isolates allowed them to be grouped into two main clusters only. The major group consisted of 19 isolates related to P. oryzihabitans, while in the minor one ten isolates related to P. putida were found together with very few other pseudomonads. Almost the same clustering was obtained a with the independent grouping methods of amplified ribosomal DNA restriction analysis (ARDRA). These results strongly indicate that mainly bacteria strains related to Pseudomonas oryzihabitans were associated with dieback-affected Dalbergia sissoo trees. Immuno-histological studies with thin-sections of sissoo roots using Pseudomonas-specific antibodies showed that bacteria had invaded the root parenchyma. Plant Tissue Cult. & Biotech. 24(2): 141-153, 2014 (December)